Governing the Sacred: Articulations between Secularism, Religion, and Power in Russia - Vasquez, Gladys Angelica (2025)
This article analyzes how the Russian State, through religious nationalism and the doctrine of Russkiy Mir, constructs a political project that articulates sovereignty, identity, and moral order through the sacralization of State power. Using a critical discourse analysis of official, religious, and media sources, it examines the practices and narratives that produce a patriotic subjectivity based on fear, loyalty, and obedience. The results show that this alliance between the Kremlin and the Russian Orthodox Church legitimizes political actions, such as the war in Ukraine, under a spiritual rhetoric that strengthens social cohesion and consolidates an exclusive moral community. It is concluded that Russkiy Mir represents a post-secular form of modernity that employs the sacred as a technology of power to offer a political model alternative to secular liberalism.